Benzosultam synthesis exploiting sequential palladium-catalysed intermolecular aminosulfonylation and intramolecular sulfamidation - Richards-Taylor, C; Willis, M (Elsevier, 2021)
We report a route to benzosultams that exploits the palladium-catalysed aminsulfonylation of alkenyl iodides as the initial step. An (Z)-configured alkenyl iodide substrate is combined with DABSO, a N,N-dialkylhydrazine nucleophile and a palladium(0) catalyst to achieve aminsulfonylation. A second palladium(0)-catalysed transformation, this time intramolecular, leads to benzosultam formation. Good variation of the starting alkenyl iodides is possible. A related SNAr route was also explored, but was shown to be less efficient.